Meeting between the Prime Minister and members of the Trades Union Congress General Council Special Industrial Committee (12 noon) (verbatim report) : (1926/04/24) - Mining Association of Great Britain ; Trades Union Congress. General Council. Special Industrial Committee
26 April 1926